2019
DOI: 10.1200/jgo.19.00142
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor Dosing: Can We Go Lower Without Compromising Clinical Efficacy?

Abstract: In just a few years, immune checkpoint inhibitors have dramatically changed the landscape in oncology, offering durable responses and improved survival for many patients across several tumor types. With more than 3,300 new agents in the immuno-oncology pipeline plus a wide array of combinations being studied, it seems this new era is just getting started. These advances come with a significant caveat: most of the world population does not have access to their benefits, because the yearly cost of a novel antica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 21 publications
1
62
0
Order By: Relevance
“…Thus, a 0.5 mg/kg Q3 W dose of pembrolizumab, which is nearly 10 times lower than the approved dose, shows 90% target engagement. 63 The absence of a dose/exposure vs efficacy dependence has also been observed in pooled analyses of Phase 1 and Phase 2 trials of pembrolizumab. 64 Similar results have been observed in Phase 1 trials of nivolumab, another approved PD-1 blocking antibody, with a dosing regimen of 0.3 mg/kg Q2 W resulting in saturating target engagement.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, a 0.5 mg/kg Q3 W dose of pembrolizumab, which is nearly 10 times lower than the approved dose, shows 90% target engagement. 63 The absence of a dose/exposure vs efficacy dependence has also been observed in pooled analyses of Phase 1 and Phase 2 trials of pembrolizumab. 64 Similar results have been observed in Phase 1 trials of nivolumab, another approved PD-1 blocking antibody, with a dosing regimen of 0.3 mg/kg Q2 W resulting in saturating target engagement.…”
Section: Discussionmentioning
confidence: 88%
“…94 These results are in excellent agreement with a growing number of clinical reports, which indicate that an adequate reduction in dose does not compromise disease control or overall survival outcome measures. 62,63,[95][96][97] The present meta-analysis, combined with quantitative population PKPD analyses of patient-level clinical data may provide a very robust framework for the further optimization of ICI dosing regimens, especially in combination settings.…”
Section: Discussionmentioning
confidence: 99%
“…The current attitude is that these drugs cost too much [ 74 ]. Renner et al, has pointed out that ICIs may reduce toxicity but they are financially toxic and high costs limit their access in many countries inside and outside the U.S. [ 77 ]. A potential drawback for targeted therapeutics, the ADCs EV and SG and, the small molecule erdafitinib are more expensive than the listed ICIs.…”
Section: Health Economic Factorsmentioning
confidence: 99%
“…[1][2][3] The widespread adoption of anti-PD-1 agents and durable responses seen in some patients have raised important questions regarding the optimal frequency of administration of these drugs, including the impact of treatment interruptions or discontinuations in routine clinical practice. 4 Although immune-related adverse events (irAEs) have been associated with improved outcomes in NSCLC 5,6 , a retrospective study in Canada suggested lower overall survival (OS) in patients receiving interrupted treatments due to irAEs. 7 Additionally, the lowest and least frequent dose of pembrolizumab that may permit maximal efficacy in advanced NSCLC is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…7 Additionally, the lowest and least frequent dose of pembrolizumab that may permit maximal efficacy in advanced NSCLC is still unknown. 4,8 Moreover, the financial and societal impacts of access to this durably efficacious therapy for this growing population necessitates thoughtful consideration of resource utilization and the patient care experience so as to afford an optimized and sustainable care paradigm for all those who may benefit. 4,9,10 Recent efforts to develop less frequent and more flexible dosing regimens have included the phase 3b/4…”
Section: Introductionmentioning
confidence: 99%